Impact of Inappropriate Transport on the Welfare and Cut Quality of Broilers: A Review - Ménard, Hansheys; Galvão, V.M.L.; Reis, A.P.; Soares, A.F. (International Journal of Poultry Science, 2025)
Since Brazil is one of the largest consumers and exporters of broiler chickens, poultry farming plays a crucial role in the Brazilian economy. However, the consumer market increasingly demands practices compatible with animal welfare. The pre-slaughter processes (handling and transport) are especially challenging for professionals of this industry. This review of the literature was aimed to highlight important aspects to improve welfare of birds during these processes. The importance of stressors such as environmental temperature, humidity, population density of vehicles and transport and failures in catching animals was discussed in this review. During harvesting, thermal stress and management failures cause a large proportion of birds to present carcass defects, such as injuries, fractures, Pale Soft and Exudative and an increase in the rate of Dead on Arrival. The high population density and inadequate distribution of animals in the transport compartment can result in the formation of heat and humidity islands and reduce ventilation efficiency, causing thermal stress to occur. Deaths can occur at any stage up to the slaughterhouse, however long journeys under inadequate transport conditions, road quality and temperature is more like to cause deaths. Logistics adaptations in the transport system and better-quality control and identification of risk factors are essential to avoid injuries and mortality of birds during transport.